Physical Activity, Sedentary Behavior, Anxiety, and Pain Among Musicians in the United Kingdom - Matei, Raluca; Ginsborg, Jane (Frontiers in Psychology, 2020)
Context and aims: Although some exercise-based interventions have been associated with lower levels of pain and performance-related musculoskeletal disorders (PRMDs) among musicians, the evidence is still mixed. Furthermore, little is known about musicians’ general engagement in physical activity (PA), their knowledge of PA guidelines, or the relevant training they receive on pain prevention and the sources of such training. Similarly, little is known about the relationship between PA and PRMDs and other risk factors for PRMDs. Methods: Following a cross-sectional correlational study design, both standardised and ad hoc measurements were used to investigate self-reported PA (IPAQ-SF), knowledge of PA guidelines, and barriers to engaging in PA (CDC; DPAQ); sedentary behaviour (SBQ); pain (SF-36) and PRMDs (frequency and severity); reported physical exertion (RPE); anxiety (HADS); practice behaviours (e.g. practice time; taking breaks frequency; warming up); and relevant training among conservatoire students in the UK. The entire set of questionnaires was administered both online and via hard copies between June 2017 and April 2018. Results: Demographic information was obtained from 111 respondents, mostly undergraduate students from seven conservatoires. They reported high levels of engagement in PA, despite poor knowledge of PA guidelines. Teachers were the most frequently mentioned source of pain prevention information (by 43% of respondents), and 62% agreed that they had received advice on why they should engage in cardio PA. Sedentary behaviour was comparable to normative data. Levels of bodily pain and PRMDs were low, but 43% showed ‘abnormal’ clinical anxiety and found playing their instruments 'somewhat hard' (RPE) on average. Bodily pain interfering with practice and performance was positively correlated with frequency and severity of PRMDs, anxiety, and RPE. Frequency and severity of PRMDs were also associated with sedentary behaviour at the weekend. Anxiety was associated with RPE. No association was found between PA and PRMDs. Conclusion: The relationship between PA and PRMDs and pain remains unclear and needs further investigation. While health education needs to be improved, other pathways may need to be taken. Given the high levels of anxiety, the ideology of Western classical music itself may need to be challenged.